Theology and Psychology in Dialogue: An Individual Differences Approach. Issue 1 (January 2016) - Francis, Leslie J.
Abstract : This paper introduces the notion of the theology of individual differences which engages a Christian understanding of human beings created in the image of God with insights derived from the psychology of individual differences.